Analisis Cost Volume Profit untuk Merencanakan Laba pada UD. Gilang Mandiri di Kabupaten Ende - Payu, Alexarina; Tanusi, Gabriel; Sari, Santy Permata (Program Studi Manajemen Universitas Flores, 2021)
The purpose of this study is to determine the cost control palnning and planning to icrease sales volume so that it affects profit earned. The type of research used in this study is quantitative descriptive research used and the dara sources used are data primary and secondary with data collection techniques through interviews and documentation. This research was conducted at UD. Giland Mandiri in Ende which is located on Wolter Mongonsidi Street No.7 Tetandara Ende. Analysis method used is quantitative descriptive analysis, namely research that aims to describe or explain events or events that occurs at the present time in the form of numbers in the UD. Independent Gilang namely data on costs, sales volume and profit during 2018 –2019 so that cann strengthen in making conclusions. Based on the results of the 2018 contribution margin analysis of Rp 530.900.000 with a contribution margin ratio of of 40,14%, contribution margin in 2019 f Rp 242.982.000 with a contribution margin ratio of 22,06%. Break even point in 2018 was Rp 288.988.540,01 and in 2019 amounting to Rp 525.838.621,94. Margin of safety in 2018 2018 was 78,14% with margin of safety 52,23% with a margin of safety in rupiah of Rp 575.052.300. the profit IDR 660.302.307,08 and Rp 2.351.274.787,43 for the 2019 profit target.